2014
DOI: 10.1590/s1517-83822014000200009
|View full text |Cite
|
Sign up to set email alerts
|

Growth kinetics, effect of carbon substrate in biosynthesis of mcl-PHA by Pseudomonas putida Bet001

Abstract: Growth associated biosynthesis of medium chain length poly-3-hydroxyalkanoates (mcl-PHA) in Pseudomonas putida Bet001 isolated from palm oil mill effluent was studied. Models with substrate inhibition terms described well the kinetics of its growth. Selected fatty acids (C8:0 to C18:1) and ammonium were used as carbon and nitrogen sources during growth and PHA biosynthesis, resulting in PHA accumulation of about 50 to 69% (w/w) and PHA yields ranging from 10.12 g L−1 to 15.45 g L−1, respectively. The monomer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 39 publications
2
35
2
Order By: Relevance
“…A remarkable peak of C=O bond in the carbonyl ester group at the wavelength of 1734.91 cm -1 was observed and this is in agreement with the FTRI spectrum of standard PHB. Absorption at 3353.91 cm -1 is due to the presence of hydroxyl group (OH -) in a polymer chain (Gumel et al, 2014;Ma et al, 2009). The wavelength at 1559.85 cm -1 (NC=O) is assigned to a protein amid the traces remaining in the cells (Colthup et al, 1990).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A remarkable peak of C=O bond in the carbonyl ester group at the wavelength of 1734.91 cm -1 was observed and this is in agreement with the FTRI spectrum of standard PHB. Absorption at 3353.91 cm -1 is due to the presence of hydroxyl group (OH -) in a polymer chain (Gumel et al, 2014;Ma et al, 2009). The wavelength at 1559.85 cm -1 (NC=O) is assigned to a protein amid the traces remaining in the cells (Colthup et al, 1990).…”
Section: Resultsmentioning
confidence: 99%
“…The FTIR results reveal that the polymer produced by Rhodotorula graminis TISTR 5124 might possibly be the copolymer PHBV, when compared to the standard PHBV shown in Figure 5. Figure 4 FT-IR spectra of PHA extracted from Rhodotorula graminis TISTR 5124 cultured in P-limited condition Figure 5 FT-IR spectra of copolymer PHBV extracted from P. putida Bet001 (Gumel et al, 2014) The extracted polymer was also determined by 1 H NMR and the result is shown in Figure 6. When compared with the NMR spectra of copolymer PHBV in Figure 7, the peaks are very similar.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A sample of dried crude extract of Neocaryamacrophylla leaves (2 mg) was dissolved in 10 ml of chloroform, the mixture was filtered using a 25 ml borosilicate glass syringe equipped with disposable PTFE filter (Ø = 0.22µm). Filtered sample in the form were used for the GC-MS analysis according reported literature (Gumel et al 2014) with slight modification. Briefly, dissolved sample (1 µl) was automatically injected into the GC- …”
Section: Phytochemical Screening Using Gc-ms Analysismentioning
confidence: 99%
“…In this study, the accumulation of PHA in Pseudomonas putida Bet001 and D. tsuruhatensis Bet002 from various types of odd and even aliphatic acids, selected sugars, and glycerol as sole carbon and energy substrate was investigated. Both microorganisms were isolated from palm oil mill effluent (POME) and showed growth-associated PHA accumulation [3,4,24]. Variables namely final total biomass, yield of PHA, monomer fraction, and polymer properties of synthesized PHA were studied.…”
Section: Pseudomonas Putida Bet001mentioning
confidence: 99%